DOSIFICADOR INTELIGENTE DE ALIMENTO CONCENTRADO PARA GANADO BOVINO (Agroindustria, Sociedad y Ambiente, 2021)
At the present time the cattle producers make the majority of the processes of feeding to the animal of artisan form (manual), this causes that they are not being adequately provided with the necessary amount causing the body mass to fall and therefore the milk production. The overall objective is to dose concentrated feed for cattle in an intelligent way in order to seek to improve dairy productivity by reducing manual feed and in turn reducing food losses. The functionality of the equipment is based on the operator supplying the quantity of milk produced by the cow and the dispensing hopper through a man / machine interface. This information reaches the control system which sends a signal to the auger to transport the food that is located in the storage hopper to the selected hopper, where the food is weighed by means of the sensors until the ideal weight is obtained, immediately sends a signal to the control system to stop the auger and open the gates of the dispensing hopper located in the feeder. In conclusion, it was possible to verify the functionality of the dispensing system of the input hopper, the weighing and dispensing hoppers, the conveyor screw, the ultrasonic sensor HC-SR04, square resistive force sensor 1.75x1.5 '' and the PIC16f877A microcontroller.
Keywords: Concentrated food, doser, microcontroller. ultrasonic sensor and resistive force sensor.